2009
DOI: 10.1007/s11274-009-9980-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of microorganisms in solar salterns of Tamil Nadu, India

Abstract: In this study, the diversity of prokaryotes inhabiting crystallizer ponds of three solar salterns, located along Bengal Bay in Tamil Nadu, India was examined. Unlike other salterns studied the Tamil Nadu salterns are fed by hypersaline spring water mixed with seawater and led to the ponds from bore wells. In addition, prokaryotic community development is restricted as salterns operate only during the arid part of the year. Both culture-based and culture-independent polymerase chain reaction 16S rRNA molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…It was significantly higher than that observed by other authors in hypersaline salterns with higher than 30% salt content of the sampling site (Table 2): three bacterial genera have been established in Maras salterns, Peru [21]; five bacteral genera in a 32% salt pond, Santa Pola salterns, Spain [19]; four bacterial genera in 30% salt ponds, Guerrero Negro saltern, Mexico [22]; and five bacterial genera in the 31% salt pond S5 from a solar saltern in Tunisia [23]. The equal number of genera (15 each) represented in both archaeal [10] and bacterial communities from PS differs from the observations of other authors that members of the domain Archaea are dominant, whereas those of the domain Bacteria are slightly represented in hypersaline environments [4,[21][22][23][24]. Like our study, Dillon et al [22] have reported similar archaeal and bacterial 16S rRNA diversity (four genera each) in a hypersaline pond in evaporative Guerrero Negro salterns.…”
Section: Salt Composition Of Watermentioning
confidence: 68%
See 1 more Smart Citation
“…It was significantly higher than that observed by other authors in hypersaline salterns with higher than 30% salt content of the sampling site (Table 2): three bacterial genera have been established in Maras salterns, Peru [21]; five bacteral genera in a 32% salt pond, Santa Pola salterns, Spain [19]; four bacterial genera in 30% salt ponds, Guerrero Negro saltern, Mexico [22]; and five bacterial genera in the 31% salt pond S5 from a solar saltern in Tunisia [23]. The equal number of genera (15 each) represented in both archaeal [10] and bacterial communities from PS differs from the observations of other authors that members of the domain Archaea are dominant, whereas those of the domain Bacteria are slightly represented in hypersaline environments [4,[21][22][23][24]. Like our study, Dillon et al [22] have reported similar archaeal and bacterial 16S rRNA diversity (four genera each) in a hypersaline pond in evaporative Guerrero Negro salterns.…”
Section: Salt Composition Of Watermentioning
confidence: 68%
“…The use of culture-independent methods for studying prokaryotic diversity based on direct polymerase chain reaction (PCR) amplification of the gene-encoding small-subunit 16S rRNA from environmental DNA samples has led to a significant improvement in the idea of the numbers of existing taxa [4]. The small deal of culturable microorganisms in comparison with the deposited sequences very often hinders setting the firm taxonomic position of the novel sequences [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to Lizama et al (2001) the most enzymatic productive strains belonged to the genus Halorubrum. In a study by Anikandan et al (2009) the high rate protease production was observed in species belonged to the Halorubrum, Haloarcula, Halobacterium genera. The results of previous studies and what was observed in this study suggest that the genus Halorubrum and Haloarcula have high rate of enzymes productions.…”
Section: Characterization Of the Isolatesmentioning
confidence: 99%
“…Ozcan et al (2006) and Birbir et al (2007) showed amylase, protease, lipase and amylase, protease, lipase cellulase, nuclease activity in the haloarchaeal strains, respectively. Anikandan et al (2009) could detect amylase, protease, Haloarcula,Natrinema,Halovivax and Natronomonas. 1,amylase;2,protease;3,lipase;4,pullulanase;5,xylanase;6,CMCase;7,chitinase;8,inulinase;9,pectinase;10 DNase but no lipase activity on the haloarchaea they isolated.…”
Section: Characterization Of the Isolatesmentioning
confidence: 99%
“…Several cultivable species from the Halobacteriaceae family have been isolated from various solar salterns belonging to the genera Haloferax, Halorubrum, Haloarcula, Halobacterium, Halogeometricum, Halosarcina, Halorubrum, Haloquadratum, and Natrinema, (Asha et al, 2005;Pašić et al, 2005;Manikandan et al, 2009;Cui et al, 2011;Trigui et al, 2011). However, different halophilic or halotolerant microbial communities are present in solar salterns and also take part in this process (Oren et al, 2009) since these habitats showed diverse groups of microorganisms (Manikandan et al, 2009), although the dominant group appears to be halophilic archaea (Pašić et al, 2005).…”
Section: Uses In Solar Salt Productionmentioning
confidence: 99%